2012
DOI: 10.1159/000341336
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Host Defense System in the Development of Cerebral Vasospasm: Analogies between Atherosclerosis and Subarachnoid Hemorrhage

Abstract: Similar to atherosclerosis, platelet-derived growth factor (PDGF)-BB, a major growth factor for vascular smooth muscle cells, is produced in arterial walls to repair arteries after subarachnoid hemorrhage (SAH). On review of a series of research articles that focus on defensive host responses to SAH, PDGF-BB is identified as a spasmogen, based on the following findings: (1) foreign substances injected into the subarachnoid space cause persistent constriction of cerebral arteries with a time course and histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 250 publications
1
8
0
Order By: Relevance
“…They are involved in a wide range of biochemical processes, including mitosis, would healing, vessel formation, and vasoconstriction. [25][26][27] Previously, PDGF levels and outcomes after aSAH have been reported 28,29 ; however, our findings pertaining to interactions between PDGFs, CCL5, sCD40L, 30 and CXCL1P1 are previously undescribed and warrant further investigation. (2) IL-2, IL-9, IL-12p40, and TNF-b cytokines: From T 1 to T 4 , a cluster including IL-2, IL-12p40, TNF-b, and IL-9 was observed.…”
mentioning
confidence: 68%
“…They are involved in a wide range of biochemical processes, including mitosis, would healing, vessel formation, and vasoconstriction. [25][26][27] Previously, PDGF levels and outcomes after aSAH have been reported 28,29 ; however, our findings pertaining to interactions between PDGFs, CCL5, sCD40L, 30 and CXCL1P1 are previously undescribed and warrant further investigation. (2) IL-2, IL-9, IL-12p40, and TNF-b cytokines: From T 1 to T 4 , a cluster including IL-2, IL-12p40, TNF-b, and IL-9 was observed.…”
mentioning
confidence: 68%
“…Studies have shown that reactive oxygen species, such as the superoxide anion (·O 2-), hydroxyl radical (·OH), and hydrogen peroxide (H 2 O 2 ), are the major factors that bind as ligands to nuclear receptors in human umbilical vein endothelial cells (HUVECs), participate and regulate the expression of several genes, enhance mononuclear cell adhesion and immigration to the vascular intima, and play a pivotal role in the initial stage of AS, diabetes, hypertension, and heart failure (Yanamoto et al, 2012;Brioschi et al, 2013;Choi et al, 2013;Montoro-García et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…DCVS following SAH is a complex pathological process, which is associated with vascular endothelial function impairment, shrinkage and proliferation of vascular smooth muscle, immune inflammatory reaction and gene regulation ( 36 ). It has previously been demonstrated that cerebrovascular endothelial cell damage is the key characteristic of cerebral artery pathology in patients following SAH ( 37 ).…”
Section: Discussionmentioning
confidence: 99%